Real Time Heart Rate Measurement and Heart Wave Drawing (ECG) Using Webcam (Al-Mansour Journal, 2022)
Medically, the doctor uses his fingers to sense patient's heart pulse for measuring heart rate manually ,also he puts electrodes on patient's body to draw the heart wave (Electrocardiography (ECG or EKG)), and both processes are (contact based system). Medically, the heart pulse causes two invisible effects on human being, the first is a slight vibration in human head (motion) and the second is a slight change in skin color due to blood flow into skin (brightness). In this paper, an algorithm was developed to measure the heart rate and draw ECG diagram by webcam in real time without using any additional hardware (non-contact based system) and it can also be developed to help the doctors to examine their patients remotely via the Internet. The proposed algorithm use motion detection technique to detect the heartbeat from webcam frames, where the neighbors frames are subtract from each other to detect the head vibration and skin color change at that moment. The output of the subtraction is converted to a binary form and the sum of the resulting pixels represents the heartbeat values which are used to measure the heart rate and draw ECG. The traditional equation of heart rate calculate the heart pulse in one minute only, but the webcam may be opened for unknown time, therefore in this algorithm the Heart rate equation was developed to calculate the Heart rate in per second instead of per minute and for unlimited time (not only for one minute). The results show that, this algorithm able to measure heart rate with error rate not exceeding (2%) and draw ECG in real time using webcam and for unlimited time.
Keywords: Heart Wave drawing; Electrocardiography (ECG or EKG); Motion detection; Heartbeats detecting; Maxima Peaks detection; Face detecting; Head vibration